1995
DOI: 10.1074/jbc.270.45.26778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based Inhibition of Yeast α-Glucosidase and Human Pancreatic α-Amylase by a New Class of Inhibitors

Abstract: A burst of release of one equivalent of trinitrophenolate observed upon inactivation of human pancreatic ␣-amylase proves the required 1:1 stoichiometry. These are the first mechanism-based inhibitors of this class to be described, and the first mechanism-based inhibitors of any sort for the medically important ␣-amylase. In addition to having potential as therapeutics, compounds of this class should prove useful in subsequent structural and mechanistic studies of these enzymes.Specific inhibitors of glycosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 25 publications
2
80
0
Order By: Relevance
“…Conceivably, D1136 pushes the −1 O2 atom towards the intermediate position, while Q1509 holds the −1 glucose O6 atom. Similar to GH13 enzymes, the C2-O2 bond of the −1 glucose residue is polarized by interactions of the O2 atom with H1135, D1136, and R1023, which lowers the energy of the transition state (14,22,33,34). The reaction is completed by nucleophilic attack of D1025 on the glucose C1 atom, which results in a covalent intermediate with the glucosyl moiety attached to D1025 via a β-glycosidic linkage.…”
Section: Resultsmentioning
confidence: 99%
“…Conceivably, D1136 pushes the −1 O2 atom towards the intermediate position, while Q1509 holds the −1 glucose O6 atom. Similar to GH13 enzymes, the C2-O2 bond of the −1 glucose residue is polarized by interactions of the O2 atom with H1135, D1136, and R1023, which lowers the energy of the transition state (14,22,33,34). The reaction is completed by nucleophilic attack of D1025 on the glucose C1 atom, which results in a covalent intermediate with the glucosyl moiety attached to D1025 via a β-glycosidic linkage.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding interactions at this position can contribute up to 48 kJ mol -1 to transition state stabilization 18,19 . These hydrogen bonds serve two purposes.…”
Section: How Cgtase Binds Its Substratementioning
confidence: 99%
“…One is the distortion of the sugar ring towards the half chair conformation. The other is a reduction in the electronegativity of the 2-hydroxyl, which otherwise strongly disfavors formation of a positively charged transition state 18,19 . CGTase reduces this electronegativity in two ways.…”
Section: How Cgtase Binds Its Substratementioning
confidence: 99%
“…The calculated binding modes of the two inhibitors in the active site of α-glucosidase are compared in Figure 6. It is seen that the 5,7-dihydroxy- [1,4]naphthoquinone moiety of 1 resides in close proximity to the catalytic residues including Asp214, Glu276, His348, and Asp349, indicating that it can serve as a surrogate for the terminal glucose with anomeric center in the substrate. Four hydrogen bonds are established between the phenolic and carbonyl oxygens of 1 and the side chains of Asp214, Thr215, Ser244, and Arg312.…”
Section: Resultsmentioning
confidence: 99%
“…Of the two popular glucosidases, α-glucosidase (EC 3.2.1.20) has drawn a special interest of the pharmaceutical research community because it was shown in earlier studies that the inhibition of its catalytic activity resulted in the retardation of glucose absorption and the decrease in postprandial blood glucose level. [3][4][5] Therefore, effective α-glucosidase inhibitors may serve as chemotherapeutic agents for clinic use in the treatment of diabetes and obesity. Due to the catalytic role in digesting carbohydrate substrates, α-glucosidase has also been well appreciated as a therapeutic target for the other carbohydrate mediated diseases including cancer, 6 viral infections, 7,8 and hepatitis.…”
Section: Introductionmentioning
confidence: 99%